2003
DOI: 10.5551/jat.10.246
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Wall Thickness is Associated with Insulin Resistance in Type 2 Diabetic Patients

Abstract: The aim of the present study was to investigate the independent association of the intimal-medial thickness of carotid and femoral arteries (CA-IMT and FA-IMT), a marker of atheroscelosis, with insulin resistance in type 2 diabetic patients. We evaluated CA-IMT and FA-IMT by high-resolution ultrasonography and insulin resistance determined by euglycemic hyperinsulinemic clamp in 119 type 2 diabetic subjects, 71 males and 48 females (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Diabetes mellitus is a well known risk factor for coronary atherosclerosis and its complications [17][18][19]. Several recent studies have evaluated and compared traditional cardiovascular risk factors in patients with CAE and in those with stenotic CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a well known risk factor for coronary atherosclerosis and its complications [17][18][19]. Several recent studies have evaluated and compared traditional cardiovascular risk factors in patients with CAE and in those with stenotic CAD.…”
Section: Discussionmentioning
confidence: 99%
“…There have been fewer studies of the clinical implications of stiffness parameter than of IMT. We and several other investigators have reported that stiffness parameter is associated with left ventricular function 30,31) , insulin resistance 22,23,32,33) , peripheral artery disease 21) , decreased GFR 20) , and drug treatments 15, 24-26, 34, 35) . These findings suggest the possible use of stiffness parameter as both a surrogate marker of atherosclerosis in treatment and a predictor of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…IR was associated with increased intimal-medial thickness of both carotid and femoral arteries in non-insulin dependent diabetes mellitus (NIDDM) patients (1). It is now generally recognized that IR is characteristic of patients with either impaired glucose tolerance or NIDDM.…”
Section: Introductionmentioning
confidence: 99%